Communication Strategy of Jaya's Main Course and Training Institute in Attracting Students to Computer Training - Hardianti, Ika; Rasyid, Abdul (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Computer training aims to develop the ability of everyone, especially in the field of computers, where computers have become a big part of a technology that cannot be separated from human life activities, both work, school and other activities. This study aims to determine how the communication strategy of the main training course institution in attracting student interest in computer training. The research method used is descriptive qualitative research method with a research focus on communication strategies with the AIDA model, namely Attention, Interest, Desire and Action. Data collection techniques are done through observation and in-depth interviews with informants face-to-face so that it will produce clear data. The research shows that the communication strategy carried out is to use an advertising strategy which includes promotion through social media instagram, facebook, youtube and website and direct marketing. The most effective strategy is direct marketing which fosters relationships so that cooperation with several schools is established. In this case, students at the Utama Jaya Course and Training Institute (LKP) have increased. Based on the results of in-depth interviews conducted directly by researchers to the management of the institution, that the communication strategy that attracts the most prospective training students is direct marketing to schools where from this collaboration the school recommends to its students, especially vocational students majoring in Computer and Network Engineering (TKJ) and Software Engineering (RPL) to take computer training at the Main Jaya Training Course Institute (LKP) with the aim that students master the material to face computer practice exams.